2017
DOI: 10.1017/s1047951117002001
|View full text |Cite
|
Sign up to set email alerts
|

Association ofCx43rs2071166 polymorphism with an increased risk for atrial septal defect

Abstract: Atrial septal defect is one of the most common CHD. The pathogenesis of atrial septal defect still remains unknown. Cx43 is the most prevalent connexin in the mammalian heart during development. Its genetic variants can cause several CHD. The aim of our study was to investigate the association of genetic variations of the Cx43 with sporadic atrial septal defect. A total of 450 paediatric patients were recruited, including 150 cases with atrial septal defect and 300 healthy controls. The promoter region of Cx43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…GJA4 (Cx37 coding gene) gene SNPs correlate with large vessel disease, such as ischemic stroke and coronary heart disease (27,28). Similarly, GJA1 gene SNPs correlate with primary hypertension, congenital heart disease, and arrhythmia (18)(19)(20). Although there is no clear clinical evidence suggesting that GJA1 gene SNPs correlate with CSVD, its biodistribution supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GJA4 (Cx37 coding gene) gene SNPs correlate with large vessel disease, such as ischemic stroke and coronary heart disease (27,28). Similarly, GJA1 gene SNPs correlate with primary hypertension, congenital heart disease, and arrhythmia (18)(19)(20). Although there is no clear clinical evidence suggesting that GJA1 gene SNPs correlate with CSVD, its biodistribution supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of in vivo and in vitro experiments suggest that Cx43 is necessary for maintaining BBB function from several aspects including ECs (11,12), astrocytes (13,14), and hemichannels (15)(16)(17). Further, single-nucleotide polymorphisms (SNPs) of the GJA1 gene (Cx43 coding gene) correlate with primary hypertension (locus rs1925223) (18), congenital heart disease (locus rs2071166) (19), and arrhythmia (locus rs1925223) (20). However, there is currently no clinical evidence showing a relationship between CSVD and Cx43, or any other Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a study of different populations, genetic factors were shown to play a large role in the pathogenesis of ASD, for either familial or sporadic cases [8] . It has been reported that SNPs in genes such as NKX2-5, GATA4, TBX-20, MYH6, MTHFR, and Cx43 are signi cantly related to the risk of ASD [9][10][11]. A recent meta-analysis found that the prevalence of congenital heart disease varies in different countries and regions [12].…”
Section: Introductionmentioning
confidence: 99%